Development of b-type and multi-ion doped carbonated hydroxyapatite bioceramics / Marjan Safarzadeh - Marjan , Safarzadeh (2020)
The present research is aimed to investigate the effect of varying the carbonate to phosphate (CO32−/ PO43‒) molar ratios from 0.5 to 5 on the physical and mechanical properties of carbonated hydroxyapatite (CHA) synthesized by a wet chemical method. The sintering was performed under dry carbon dioxide atmosphere at 900 °C to maintain the B-type CHA structure. It was found that increases in CO32−/ PO43‒ ratio was accompanied by an increase in the c/a lattice ratio. The diffraction peaks of the synthesized 0.5-5 CHA powders exhibited a single phase material except for 5CHA which revealed the some minor calcite or (CaCO3) as a secondary phase. The sintering studies indicated that all CHA was thermally stable and retained the apatite structure after sintering. The relative density of the sintered CHA was found to decrease along with the Vickers hardness and fracture toughness as the CO32−/ PO43‒ ratio increased from 0.5 to 4. The improvement in the mechanical properties was associated with improvement in the relative density and the larger grain size of the sintered samples. The CHA with upper limit of carbonate was chose as the optimum CHA for the next investigations. Subsequently, evaluate the effect of varying sintering temperature (800 °C, 900 °C, 1000 °C and 1100 °C) under the dry CO2 atmosphere on the compacted CHA sample. The results shown that all samples retained single phase B-type CHA except at 1100 °C which was accompany with the formation of CaO in the apatite structure. Increasing sintering temperature led to a gradual decrease in the carbonate content of the CHA pellets and an increase in mechanical properties up to 1000 °C. In particular, the HV and KIc values increased with increasing sintering temperature. An in vitro bioactivity test was evaluated on the 0.5-4 CHA pellets using simulated body fluid (SBF) solution. It was found that increasing the carbonate content enhanced the solubility of CHA pellets and increased the thickness of the apatite layer on the sample’s surface. Lastly the effect of multi-ions (Mg2+, SiO44-, Zn2+ and Cu2+) doping on the properties of carbonated hydroxyapatite (CHA) prepared by a wet chemical method was investigated. Different combinations of ions were doped into the CHA and the as-synthesized compacts were sintered at 900 °C and wet CO2 atmosphere prior to body characterization. It was found that regardless of ions doping, the lattice structure of the CHA was not disrupted. In addition, secondary phases were not detected for all the multi-ions doped samples. The XRD and FTIR results further confirmed the presences of a B-Type CHA in the as-synthesized and sintered samples. The XRD analysis revealed that the lattice parameters (c/a ratio) increased with dopant addition and resulted in a smaller crystallite size. The FESEM examination also showed the presences of smaller grain size for the multi-ions doped CHA samples thus indicating that the doping was beneficial in suppressing grain coarsening in carbonated hydroxyapatite. The main advantageous of this synthesis method is low production costs and relatively time-saving that exhibited higher mechanical properties at lower sintering temperature in CO2 atmosphere. Additionally, the presence of minor elements in CHA is more promising to enhance biomedical properties.